ANALISIS KINERJA SIMPANG TIGA TAK BERSINYAL - Helwiyah Zain; Meliyana Meliyana; Muhaimin Muhaimin (Center for Research and Community Service (LPPM) University of Abulyatama, 2016)
Simpang Lamlo is one of No-Signal Three-way Junctions in National Road from Banda Aceh to Medan as a Main road and is connected directly to the Cross-Regional Road that is from Beureuneun to Geumpang as the Minor Road and vice versa. The purpose of this study is to analyze the performance of the No-Signal Three-Way Junctions by using the Indonesian Highway Capacity Manual 1997. Data required in this study are primary and secondary data. The primary data is in the form of the condition data of traffic, intersection geometric, and environment. Secondary data includes the population growth and the map of the road network. Traffic data were collected by using video recording on Monday, Wednesday and Saturday at 7.00 a.m. – 9.00 a.m., 12.00 p.m. – 2.00 p.m and 5.00 p.m. – 7.00 pm. These data were processed by using Microsoft Excel based on MKJI 1997 and and the results were made in the form of tables and graphics. From the tables and graphics, it could be known for the traffic volume, composition, and the peak hours occured in the intersections. The calculation on the peak hour with the current highest peak is on Monday, 5.00 p.m. - 6:00 p.m. in which the traffic volume at the intersection is 2737 (smp / hour). The capacity value of the existing condition in Simpang Lamlo is 2762 (smp / hour). The traffic delay in the intersection is 11,63 (det / smp). The degree of saturation at the existing condition is 0.99, higher than the provision in Indonesian Highway Capacity Manual which is 0,75. The intersection delay value is 15.64 (det / smp) and the queue chance at the intersection is 39,43% to 77,98%,